Cohesin complexes with a potential to link mammalian meiosis to cancer - Alexander Strunnikov (Cell Regeneration, 2013)
Among multiple genes aberrantly activated in cancers, invariably, there is a group related to the capacity of cell to self-renewal. Some of these genes are related to the normal process of development, including the establishment of a germline. This group, a part of growing family of Cancer/Testis (CT) genes, now includes the meiosis specific subunits of cohesin complex. The first reports characterizing the SMC1 and RAD21 genes, encoding subunits of cohesin, were published 20 years ago; however the exact molecular mechanics of cohesin molecular machine in vivo remains rather obscure notwithstanding ample elegant experiments. The matters are complicated by the fact that the evolution of cohesin function, which is served by just two basic types of protein complexes in budding yeast, took an explosive turn in Metazoa. The recent characterization of a new set of genes encoding cohesin subunits specific for meiosis in vertebrates adds several levels of complexity to the task of structure-function analysis of specific cohesin pathways, even more so in relation to their aberrant functionality in cancers. These three proteins, SMC1β, RAD21L and STAG3 are likely involved in a specific function in the first meiotic prophase, genetic recombination, and segregation of homologues. However, at present, it is rather challenging to pinpoint the molecular role of these proteins, particularly in synaptonemal complex or centromere function, due to the multiplicity of different cohesins in meiosis. The roles of these proteins in cancer cell physiology, upon their aberrant activation in tumors, also remain to be elucidated. Nevertheless, as the existence of Cancer/Testis cohesin complexes in tumor cells appears to be all but certain, this brings a promise of a new target for cancer therapy and/or diagnostics.